2013
DOI: 10.7860/jcdr/2013/5671.3302
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Blood Flow Measurements in Stable Full Term Small for Gestational Age Neonates

Abstract: Background: Cardiac blood flow measurements are useful in the haemodynamic management of neonates. Cardiac blood flows can be estimated with functional echocardiography as follows; flow in Superior Vena Cava (SVC), Right Ventricular Outflow (RVO) and Left Ventricular Outflow (LVO). Studies in preterm infants have shown that abnormal superior vena cava flow is associated with poor neurodevelopmental outcomes. To date, normative data on LVO, RVO and SVC flows has been established for term appropriate for gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…It is known that they can show differences by multiple causes, including gestational age, birth weight, medical conditions, PDA flow, and imaging modalities. 33 34 Our results are meaningful in that chronologic neonatal changes of systolic, diastolic, and TDI parameters are represented within early postnatal period with short-term intervals. They can be used to compile normal baseline data of neonates.…”
Section: Discussionmentioning
confidence: 58%
“…It is known that they can show differences by multiple causes, including gestational age, birth weight, medical conditions, PDA flow, and imaging modalities. 33 34 Our results are meaningful in that chronologic neonatal changes of systolic, diastolic, and TDI parameters are represented within early postnatal period with short-term intervals. They can be used to compile normal baseline data of neonates.…”
Section: Discussionmentioning
confidence: 58%
“…This is also evident from several studies reporting NP-POCU experiences in Indian NICUs in recent years. 14-16 As per a recent survey from the Australia–New Zealand region, the number of NICUs having at least 1 clinician with functional echocardiography skills has increased from 40% to more than 90% of units in a period of 10 years. 9, 17…”
Section: Discussionmentioning
confidence: 99%
“…Babies developing low SVC flow are less likely to have completed antenatal steroids and less likely to be born to a mother on antihypertensive medication (38,40). Interestingly, although babies developing low SVC flows are more likely to be of lower birthweight (40), a study performed solely on growthrestricted infants showed that symmetrically small infants had significantly higher SVC flow than those babies who were asymmetrically small (50). Interestingly, although babies developing low SVC flows are more likely to be of lower birthweight (40), a study performed solely on growthrestricted infants showed that symmetrically small infants had significantly higher SVC flow than those babies who were asymmetrically small (50).…”
Section: Risk Factors For Low Superior Vena Cava Flowmentioning
confidence: 99%
“…Lower gestational age, larger PDA and failure of early PDA constriction are also known to be risk factors for low flow in the SVC (14,16,38,40). Interestingly, although babies developing low SVC flows are more likely to be of lower birthweight (40), a study performed solely on growthrestricted infants showed that symmetrically small infants had significantly higher SVC flow than those babies who were asymmetrically small (50). This observation may relate more to the nature of foetal growth or the underlying cause of growth restriction rather than birthweight per se, with recent evidence showing that growth-restricted babies have complex changes in the nature of the cardiovascular system (51)(52)(53)(54).…”
Section: Risk Factors For Low Superior Vena Cava Flowmentioning
confidence: 99%